Thermal stress analysis in die-attached β-Ga2O3 using Raman spectroscopy. (1st June 2023) - Uchida, Tomoyuki; Sugie, Ryuichi
Abstract: We determine the stress deformation potentials using micro-Raman spectroscopy and evaluate thermal stress in a (−201) plane β -Ga2 O3 mounted on a Cu plate with a Pb-free solder. We conduct four-point bending tests and thermomechanical experiments to experimentally determine the stress deformation potentials of Ag (4), Ag (5) and Ag (6) modes. Based on experimental results, we estimate the suitable phonon modes for evaluating the stress, and we apply confocal Raman measurements to a β -Ga2 O3 chip mounted on a Cu plate with a Pb-free solder. In accordance with the theoretical relation between the phonon frequency shifts and the stress, we obtain the stress components in the (−201) plane β -Ga2 O3 using the peak frequency shift of Ag (4) and Ag (5) modes. The stress components in the (−201) plane is almost same, regardless of the thermal expansion anisotropy of β -Ga2 O3, and the results are consistent with those of the finite element method.